Improved thermoelectric power measurements using a four-point technique - Corcoran,J; Raja,S; Nagy,PB (NDT and E International, 2017)
The Seebeck coefficient of a material is dependent on its composition and microstructure and is consequently sensitive to service related material degradation; of particular interest is the sensitivity to thermal and irradiation embrittlement which may be exploited for the material characterisation of in service components. Conventionally, thermoelectric measurements are taken using a two-point contact technique which introduces a temperature differential in the test component through a heated ‘hot tip’ electrode; it is argued that measurements using this methodology are sensitive to the thermal contact resistance between the component and the electrodes. An alternative three- or four-point technique is proposed where heat is introduced to the component remotely which leads to much less sensitivity to contact condition. An experiment is presented that compares the two techniques and demonstrates the improved performance of the four-point technique. Aside from the improved accuracy, the modified technique also facilitates a ‘passive’ implementation that could be used from continuous monitoring of components in service.